2019
DOI: 10.3389/fendo.2019.00480
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin: Clinical Perspectives in Neurodegeneration

Abstract: Prevention of neurodegenerative diseases is presently a major goal for our Society and melatonin, an unusual phylogenetically conserved molecule present in all aerobic organisms, merits consideration in this respect. Melatonin combines both chronobiotic and cytoprotective properties. As a chronobiotic, melatonin can modify phase and amplitude of biological rhythms. As a cytoprotective molecule, melatonin reverses the low degree inflammatory damage seen in neurodegenerative disorders and aging. Low levels of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
141
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(147 citation statements)
references
References 244 publications
(187 reference statements)
2
141
0
4
Order By: Relevance
“…*P < 0.05; **P < 0.01; ***P < 0.001. degenerative models (34,(60)(61)(62). Melatonin, at the pharmacologic dose used to exert antiinflammatory effects, likely saturates the melatonin receptor (63). Thus the melatonin effects likely include both receptor-mediated and non-receptor-mediated melatonin effects, including protecting mitochondria by scavenging ROS, inhibiting the mitochondrial permeability transition pore, and activating uncoupling proteins, which maintains the optimal mitochondrial membrane potential (37).…”
Section: Discussionmentioning
confidence: 99%
“…*P < 0.05; **P < 0.01; ***P < 0.001. degenerative models (34,(60)(61)(62). Melatonin, at the pharmacologic dose used to exert antiinflammatory effects, likely saturates the melatonin receptor (63). Thus the melatonin effects likely include both receptor-mediated and non-receptor-mediated melatonin effects, including protecting mitochondria by scavenging ROS, inhibiting the mitochondrial permeability transition pore, and activating uncoupling proteins, which maintains the optimal mitochondrial membrane potential (37).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, animal studies have shown melatonin to be an effective neuroprotectant in a number of neurodegenerative conditions such as hypoxia/ischemia [5][6][7], Alzheimer's Disease [8], Parkinson's Disease [9], and spinal cord injury [10]. Notably, clinical trials have been designed to establish the potential neuroprotective efficacy of melatonin in humans [11].…”
Section: Introductionmentioning
confidence: 87%
“…These rhythms are involved in aging, carcinogenesis, and a number of diseases [4,[10][11][12][13][14][15][16]. Clinical research is underway in various fields including the application of melatonin in treating biological rhythm abnormalities, glucose and lipid metabolism disorders, immunoregulation, anticancer effects and aging-related diseases (Parkinson's and Alzheimer's disease) [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%